2020
DOI: 10.1088/1757-899x/898/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Simulation modelling as a method of risk analysis in real estate valuation

Abstract: The advent of the fourth industrial revolution was marked by the fact that changes became the main characteristics of the new time. It means a high level of uncertainty and instability in the business environment. The real estate market, being a part of the investment market, is changing. The current development of Russia’s investment potential leads to an increasing need for professional management of the profitability of such investments. Thus, the main goal of this research is to present non-traditional met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Guan et al (2014) revealed that data mining and analysis approaches are driven by artificial intelligence that originated from data scientists has been tested as a preferable solution for real estate professionals for analysing big data. McCluskey et al (2013) and Gromova and Pupentsova (2020) opined that different modern data analysis and mining techniques are driven by artificial intelligence utilised by real estate professionals. The most popular artificial neural network (ANN) originated from the data scientist domain established to replicate human cognitive functioning.…”
Section: Adoption Of Data Science Techniques For Real Estate Professi...mentioning
confidence: 99%
See 4 more Smart Citations
“…Guan et al (2014) revealed that data mining and analysis approaches are driven by artificial intelligence that originated from data scientists has been tested as a preferable solution for real estate professionals for analysing big data. McCluskey et al (2013) and Gromova and Pupentsova (2020) opined that different modern data analysis and mining techniques are driven by artificial intelligence utilised by real estate professionals. The most popular artificial neural network (ANN) originated from the data scientist domain established to replicate human cognitive functioning.…”
Section: Adoption Of Data Science Techniques For Real Estate Professi...mentioning
confidence: 99%
“…Lee and Park (2020) discovered that effective data management is crucial for adopting modern data analysis techniques for real estate professionals. Poursaeed et al (2018) and Gromova and Pupentsova (2020) discovered that the data management technique adopted by a real estate professional is vital in the performance of modern data analysis like ANN, CNN and others. Furthermore, Kasprzak (2021) affirmed that effective data management is essential for the transformation of real estate practice in the fourth industrial revolution era.…”
Section: Component 2: Data Management Systemmentioning
confidence: 99%
See 3 more Smart Citations